2014
DOI: 10.1021/jp5010133
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Phase Behavior and Maximally Random Jammed State of Truncated Tetrahedra

Abstract: Numerous recent investigations have been devoted to the determination of the equilibrium phase behavior and packing characteristics of hard nonspherical particles, including ellipsoids, superballs, and polyhedra, to name but just a few shapes. Systems of hard nonspherical particles exhibit a variety of stable phases with different degrees of translational and orientational order, including isotropic liquid, solid crystal, rotator and a variety of liquid crystal phases. In this paper, we employ a Monte Carlo im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 78 publications
1
74
0
Order By: Relevance
“…Hard nonspherical particles exhibit a richer phase diagram than that of hard spheres because the former can possess different degrees of translational and orientational order; see Refs. 74,281,283,285,289,291,299,300,302,306,307,[310][311][312]314, and 317. Nonsphericalparticle systems can form isotropic liquids, a variety of liquid-crystal phases, rotator crystals, and solid crystals.…”
Section: B Equilibrium and Metastable Phase Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Hard nonspherical particles exhibit a richer phase diagram than that of hard spheres because the former can possess different degrees of translational and orientational order; see Refs. 74,281,283,285,289,291,299,300,302,306,307,[310][311][312]314, and 317. Nonsphericalparticle systems can form isotropic liquids, a variety of liquid-crystal phases, rotator crystals, and solid crystals.…”
Section: B Equilibrium and Metastable Phase Behaviormentioning
confidence: 99%
“…300 A study of the entire phase diagram of truncated tetrahedra showed that the system undergoes two first-order phase transitions as the density increases: first a liquid-solid transition and then a solid-solid transition. 314…”
Section: B Equilibrium and Metastable Phase Behaviormentioning
confidence: 99%
“…2 for a vivid illustration. During the last decade, a variety of disordered hyperuniform states have been identified that exist as both equilibrium and nonequilibrium phases, including maximally random jammed particle packings [33][34][35][36], jammed athermal granular media [37], jammed thermal colloidal packings [38,39], cold atoms [40], transitions in nonequilibrium systems [41,42], surfaceenhanced Raman spectroscopy [43], terahertz quantum cascade laser [44], wave dynamics in disordered potentials based on supersymmetry [45], avian photoreceptor patterns [46], and certain Coulombic systems [47]. Moreover, disordered hyperuniform materials possess novel physical properties potentially important for applications in photonics [25][26][27]48,49] and electronics [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…For example, while bulk MRJ packings of nonspherical particles that span a wide range of shapes, including ellipsoids [78][79][80], superballs [81,82], and polyhedra [24,25,72,83] have been studied in detail, nothing is known about confined MRJ packings of nonspherical particles. Understanding how confined MRJ packings of nonspherical particles differ from their bulk counterparts and confined MRJ sphere packings are outstanding questions.…”
Section: Discussionmentioning
confidence: 99%